Hubungan Yesus Kepada Tuhan Dan Solidaritas Dengan Anak-Anak Dalam Ibrani 2:13: Memahami Penggunaan Perjanjian Lama Dalam Perjanjian Baru - Elvi Krisnawati Gea (Universitas Katolik Widya Karya Malang, 2023)
The New Testament is the main source in understanding Christology which is the science of theology that talks about Christ the Messiah. Talking about Christology, the letter to Hebrews has the highest Christology. In Hebrews 2:13 the author understands it as